Variants at multiple loci implicated in both innate and adaptive immune responses are associated with Sjögren's syndrome (2013)
Sjögren's syndrome is a common autoimmune disease (affecting ?0.7% of European Americans) that typically presents as keratoconjunctivitis sicca and xerostomia. Here we report results of a large-scale association study of Sjögren's syndrome. In addition to strong association within the human leukocyte antigen (HLA) region at 6p21 (P meta = 7.65 × 10 -114), we establish associations with IRF5-TNPO3 (P meta = 2.73 × 10 -19), STAT4 (P meta = 6.80 × 10 -15), IL12A (P meta = 1.17 × 10 -10), FAM167A-BLK (P meta = 4.97 × 10 -10), DDX6-CXCR5 (P meta = 1.10 × 10 -8) and TNIP1 (P meta = 3.30 × 10 -8). We also observed suggestive associations (P meta less than 5 × 10 -5) with variants in 29 other regions, including TNFAIP3, PTTG1, PRDM1, DGKQ, FCGR2A, IRAK1BP1, ITSN2 and PHIP, among others. These results highlight the importance of genes that are involved in both innate and adaptive immunity in Sjögren's syndrome. © 2013 Nature America, Inc. All rights reserved.